Reflections on the Other Side. A Southern Iberia Origin for the First Pottery Production of Northern Morocco? - Martínez Sánchez Rafael M. (Open Archaeology, 2021)
This work is a starting point for rethinking the role of the Iberian Peninsula in the neolithisation of northern Morocco. It focuses on the similarities and divergences between the first pottery productions and their decorations in both territories. This relationship is supported by the existence of an accurate chronological gradation between the first evidence of Neolithisation in Iberian Peninsula and that of northern Morocco which suggests a north–south direction. We also present arguments on the possible links between the early ceramics from the north of Morocco and those from the south of Iberia, providing a first approach to an issue that will need to be carefully analysed in future research.